1999
DOI: 10.1038/sj.bjp.0702653
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of epidermal homeostasis through P2Y2receptors

Abstract: 1 Previous studies have indicated a role for extracellular ATP in the regulation of epidermal homeostasis. Here we have investigated the expression of P2Y 2 receptors by human keratinocytes, the cells which comprise the epidermis. 2 Reverse transcriptase-polymerase chain reaction (RT ± PCR) revealed expression of mRNA for the G-protein-coupled, P2Y 2 receptor in primary cultured human keratinocytes. 3 In situ hybridization studies of skin sections revealed that P2Y 2 receptor transcripts were expressed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
110
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(121 citation statements)
references
References 42 publications
10
110
1
Order By: Relevance
“…These elevated levels of ATP in the skin can further be augmented by keratinocytes and endothelial cells, which both have been shown to be a source for ATP (35)(36)(37). Thus, this localized immune reaction is able to produce enough ATP, which may reach the serum causing activation of Tregs in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…These elevated levels of ATP in the skin can further be augmented by keratinocytes and endothelial cells, which both have been shown to be a source for ATP (35)(36)(37). Thus, this localized immune reaction is able to produce enough ATP, which may reach the serum causing activation of Tregs in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that P2 receptors are expressed in keratinocytes (17,18), but little is known about their physiological significance. During studies to clarify the role of ATP released from keratinocytes, we found that ATP produced IL-6 through P2Y 2 / P2Y 4 receptors in HaCaT keratinocytes (19).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that mechanosensitive ATP release in keratinocytes primarily auto-stimulates P2Y2 receptors and concomitantly triggers Ca 2+ influx through Ca 2+ -permeable channels (Koizumi et al, 2004;Yoshida et al, 2006;Tsutsumi et al, 2009;Boucher et al, 2010;Azorin et al, 2011;Takada et al, 2012;Ho et al, 2013), which then initiates cell migration, the primary process in the wound healing cascade (Dixon et al, 1999;Burrell et al, 2003;Burrell et al, 2005;Braun, et al, 2006;Boucher et al, 2010). We recently suggested that stretch-induced ATP release and a subsequent Ca 2+ increase mediated by P2Y activation (ATP-Ca 2+ signaling) were involved in wound closure in HaCaT keratinocytes (Takada et al, 2012).…”
Section: Introductionmentioning
confidence: 99%